A global forum on ultramafic ecosystems: from ultramafic ecology to rehabilitation of degraded environments. Issue 3 (21st May 2018) - Echevarria, Guillaume; Baker, Alan J. M.; Boyd, Robert S.; van der Ent, Antony; Mizuno, Takafumi; Rajakaruna, Nishanta; Sakaguchi, Shota; Bani, Aida
Abstract: The 9th International Conference on Serpentine Ecology (ICSE) was held in Tirana and Pogradec (Albania) from June 5 to 9, 2017. More than 100 delegates from 29 countries around the world gathered to present their research on recent advances in: (i) ultramafic soils, (ii) biogeochemistry, (iii) diversity of ultramafic flora, microflora and fauna, (iv) ecophysiology of ultramafic‐adapted organisms, (v) interactions between ultramafic organisms and their ecology, (vi) nature rehabilitation of degraded ultramafic environments (resulting from mining activities), and (vii) the production of bio‐based metals through agromining technology. Additionally, the ICSE featured the first symposium on ultramafic aquatic ecology and ecotoxicology. Albania has one of the most diverse ultramafic floras in Europe. During the conference delegates visited some of the most emblematic ultramafic sites in Albania as well as the first agromining field trial in Europe. Here, we present the major topics and provide some highlights of the 25 contributions in this Special Issue (Vol. 33 no.3 and 4).